Засоби актуалізації виражально-експресивних можливостей газетних заголовків (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
Studing of language pacularities of newspapers shows the increasing of emotive evaluation of newspaper’s head-lines due to specific syntactic constructions, due to usage of big quantity of lexico-phraseological devices and stylistic means.